Penegakan Hukum Pemalsuan Data Pada E-Commerce Dalam Sistem Multi Level Marketing Perusahaan PT. Mulia Rejeki Waterindo - Gladyswidya Wiratamia; Umar Al Haddad; Tresia Elda (JOURNAL of LEGAL RESEARCH, 2019)
AbstractElectronic crime is an act that can be ensnared by the Information and Electronic Law. This study explains the extent to which the ITE Law provides legal protection for e-commerce users and presents a solution to meet the compensation for the victims of the crime of falsification of electronic data in the case of PT. NOBLE REJEKI WATERINDO. The approach used in this research is juridical normative through library research with qualitative research methods. The results of this study indicate that legal protection for e-commerce users under the ITE Law can be strengthened by making electronic contracts. For the fulfillment of victims' compensation in the case of PT. MULIA REJEKI WATERINDO can go through a civil suit or a request for restitution. This is because in the final decision of the case the application for compensation compensation was not submitted.Keywords: Law Enforcement, Crime, Data Counterfeiting, E-commerce, Multi Level Marketing